Effectiveness of an oral health education video to dispel myths and misconceptions associated with natal teeth in a rural Nigerian community - Bankole, Olubunmi; Lawal, Folake; Ibiyemi, Olushola (International Association for Dental Research (Nigeria Division), 2024)
ABSTRACT Objective: Innovative ways are imperative to dispel myths and misconception about natal teeth in rural communities and improve maternal and child health. The aim of the study was to test effectiveness of Adunni a culturally appropriate video developed to dispel myths and misconceptions associated with natal teeth in a rural community.   Methods: This intervention study was conducted among 44 mothers attending the immunization clinic of a rural Nigerian community. The intervention was Adunni, a 28-minute culturally appropriate video developed in Yoruba language. The video was shown to mothers and a 16-item questionnaire used to assess knowledge regarding natal teeth pre- and at three weeks post-intervention. A score of one was allotted to each correct response to questions and zero for wrong answers. Data obtained was analyzed using SPSS.  Results: The mean age of participants was 28.6±8.2 years. There was improvement in knowledge of reasons for natal teeth from 22(50.0%) participants stating it is an evil and 16(36.4) as individual variation pre-intervention to 3(6.8%) and 41(93.2%) respectively post intervention (p<0.001). Overall, pre-intervention knowledge score ranged from 0–7 (mean score=2.4±2.0,95%CI=1.8–3.0) while post intervention score ranged from 1–7 (mean score=5.3±1.8,95%CI=4.7–5.8). There was a statistically significant difference between pre-and post-intervention scores (mean difference=2.9±2.4,95%CI =2.1–3.6,t=7.683,p<0.001).  Cohen’s d was 1.2. Conclusion: We found that Adunni, a videotape on dispelling myths and misconception of natal teeth, significantly improved knowledge of causes and intended practices of participants in a rural community towards infants with natal teeth with a good effect size.